Ejercicios isométricos para fortalecimiento muscular en adultos con gonartrosis. Centro de Salud Espoch Lizarzaburu-Riobamba, 2018 - Paredes Loza, María Cristina (2019)
The project Isometric exercises for muscle strengthening in adults with gonarthrosis, at Espoch Lizarzaburu HHealth Center in Riobamba, 2018, has as objective to apply the technique of Muller Hettinger to strengthen the muscles adjacent to the knee joint to reduce the effects caused by gonarthrosis in 25 patients selected with inclusion and exclusion criteria based on age and degree of evolution of the pathology. The knee joint a complex structure disposed to arthrosis; gonarthrosis, osteoarthritis of the knee or osteoarthritis, it is characterized by being a progressive degenerative process of articular cartilage, also it has a higher prevalence in women and it is common after the age of 50; There are activities that influence their development, such as climbing up and down steps, walking on uneven surfaces or spending long periods of time on their feet. The methodology used includes some types, levels, designs, approaches, methods, techniques and specific research instruments that together allowed the successful development of the entire project. In the results obtained, patients presented decreased pain, increased muscle strength, mobility arcs, as a consequence improved stability and functionality; for this reason it can be determined that the Muller Hettinger technique as part of a physiotherapeutic treatment in gonarthrosis provides us with several benefits.